Comparison of the Phase Transition and Degradation of Methylene Blue of TiO2, TiO2/Montmorillonite Mixture and TiO2/Montmorillonite Composite - Zeng, Li; Sun, Hongjuan; Peng, Tongjiang; Lv, Xia (Frontiers in Chemistry, 2019)
Nano-TiO2 (T), TiO2/montmorillonite mixture (Mix) and TiO2/montmorillonite composite (Com) were prepared by using TiOSO4•2H2O as the precursor of TiO2 and montmorillonite as the matrix. The phase transition process of TiO2 and the degradation of methylene blue (MB) in T, Mix and Com were studied by X-ray diffraction (XRD), Infrared spectrum (IR), Scanning electron microscopy with energy spectrum (SEM-EDS) and other methods. The results show that, except the heating temperature has a great influence on the phase transition and grain growth of TiO2, the introduction of montmorillonite has an obvious inhibition effect on the phase transition and grain growth of TiO2, and the inhibition effect of the Com is obviously stronger than that of the Mix. In Com, Ti-O-Si chemical bond formed between TiO2 and oxygen atoms with negative charge on the bottom of the structure layer of montmorillonite, which is the main reason for inhibition effect. However, in Mix, TiO2 only covers the surface of montmorillonite without breaking the degree of order of montmorillonite and forming no chemical bond with montmorillonite, so the inhibition effect is small. From degradation of MB, it was found that before the structure of montmorillonite was destroyed (400-600°C), the degradation ratio in Mix (85.3-99.5%) was higher than that of T and Com. At high temperature (above 700°C), because of the inhibition effect, the degradation of MB in Com is much larger than T and Mix, even after 1100°C, the degradation rate can still reach at 47%. Therefore, in industrial applications, Mix and Com can be selected to degradation MB according to the actual application temperature range.